2018
DOI: 10.1111/nyas.13942
|View full text |Cite
|
Sign up to set email alerts
|

Sm‐p80‐based schistosomiasis vaccine: double‐blind preclinical trial in baboons demonstrates comprehensive prophylactic and parasite transmission‐blocking efficacy

Abstract: Schistosomiasis is of public health importance to an estimated one billion people in 79 countries. A vaccine is urgently needed. Here, we report the results of four independent, double-blind studies of an Sm-p80-based vaccine in baboons. The vaccine exhibited potent prophylactic efficacy against transmission of Schistosoma mansoni infection and was associated with significantly less egg-induced pathology, compared with unvaccinated control animals. Specifically, the vaccine resulted in a 93.45% reduction of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 48 publications
2
44
0
2
Order By: Relevance
“…Data from several murine and nonhuman primate studies showed prophylactic, therapeutic, anti-pathology and transmission-blocking efficacies as demonstrated by significant reduction in adult worms, killing of established worms [47], reduction in tissue egg load and fecal egg excretion [14]. Recently, in a double-blind preclinical trial, baboons immunized with Sm-p80/GLA-SE had a 93.45% reduction in adult female worms with a consequent 89.95% reduction in tissue egg load [48]. The authors also reported a significant reduction in hatching rates of eggs excreted in feces [48].…”
Section: Schistosoma Mansoni Calpainmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from several murine and nonhuman primate studies showed prophylactic, therapeutic, anti-pathology and transmission-blocking efficacies as demonstrated by significant reduction in adult worms, killing of established worms [47], reduction in tissue egg load and fecal egg excretion [14]. Recently, in a double-blind preclinical trial, baboons immunized with Sm-p80/GLA-SE had a 93.45% reduction in adult female worms with a consequent 89.95% reduction in tissue egg load [48]. The authors also reported a significant reduction in hatching rates of eggs excreted in feces [48].…”
Section: Schistosoma Mansoni Calpainmentioning
confidence: 99%
“…Recently, in a double-blind preclinical trial, baboons immunized with Sm-p80/GLA-SE had a 93.45% reduction in adult female worms with a consequent 89.95% reduction in tissue egg load [48]. The authors also reported a significant reduction in hatching rates of eggs excreted in feces [48]. In another recent study designed to mimic field scenario of schistosomiasis vaccine deployment, it was shown that Sm-p80-based vaccination following PZQ treatment of chronically-infected baboons caused a significant reduction in tissue egg retention and hatching rates when subsequently challenged with S. mansoni cercariae [49].…”
Section: Schistosoma Mansoni Calpainmentioning
confidence: 99%
“…In this study, baboons selected for the co-infection group did not undergo deworming and specific-pathogen-free baboons were utilized for the single infection group. We subsequently exposed all baboons to 1000 S. mansoni cercariae percutaneously as previously described [7]. Eight weeks after infection with S. mansoni, necropsies were performed.…”
Section: Parasite Challenge and Necropsymentioning
confidence: 99%
“…For determination of schistosome egg burden in tissue, liver samples were digested overnight in 4% potassium hydroxide at 37 °C without CO 2 . This suspension was then washed and resuspended with a solution of 1.2% (w/v) NaCl and eggs were enumerated under light microscopy to determine the number of eggs per gram of tissue [7]. Excised spleen samples and mesenteric lymph nodes were mashed through nylon cell strainers and stored in freezing media until RNA purification for RNA-sequencing.…”
Section: Parasite Challenge and Necropsymentioning
confidence: 99%
“…Furthermore, it has also been shown that Sm-p80 has a therapeutic effect in vaccinated baboons through decreasing the numbers of established worms, reducing the retention of eggs in tissues and decreasing the number of eggs excreted in faeces [112]. More recent data on recombinant Sm-p80 showed a worm reduction of 33.33% -53.13% and 38% in mice and baboon respectively [113,114] and also in baboon significant reduction in hepatic egg (67.7%) [115] and 93.45% reduction on pathology producing female worms was reported [116]. Moreover, vaccine immunogenicity of Sm-p80 was assessed using RNA sequencing and it is revealed that the vaccine candidate induced both cellular and humoral immune response and a predominant Th1,Th2 and Th17 gene signature was obtained [117].…”
Section: Strategies For the Development Of Novel Vaccines For Schistomentioning
confidence: 98%